Influencers and Politics: Their Role as Political Communications in the Digital Age - Dafrizal, Dafrizal; Mastanora, Refika; Andriani, Yuli; Armadila, Armadila; Alfriani, Ranti Dwi (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
The role of influencers Regional Head Elections in Indonesia has become a topic of interest in political and social discussions. In the digital and social media era, influencers play an important role in shaping public opinion and informing voters, especially the younger generation, about various political, social and economic issues that are key points in the election. This research aims to analyze the extent of the role of influencers in shaping public opinion in the digital era during the 2024 Regional Head Elections campaign. The research method used is a descriptive approach qualitative method with data collection through observation and content analysis on the Instagram social media platform. The results showed that the presence of influencers on social media has a significant influence in shaping public opinion, especially among the younger generation such as millennials and Gen Z. Influencers act as a communication bridge between politicians and the public, disseminating political information in an innovative and interesting way so as to increase political participation. The emotional connection built between influencers and their followers makes political messages better received.